Synovial fluid matrix metalloproteinase-2 and -9 activities in dogs suffering from joint disorders - MURAKAMI, Kohei (J Vet Med Sci, 2016)
The activity of matrix metalloproteinase (MMP)-2 and MMP-9 in synovial fluids (SF) sampled from dogs with joint disorders was investigated by gelatin zymography and densitometry. Pro-MMP-2 showed similar activity levels in dogs with idiopathic polyarthritis (IPA; n=17) or canine rheumatoid arthritis (cRA; n=4), and healthy controls (n=10). However, dogs with cranial cruciate ligament rupture (CCLR; n=5) presented significantly higher pro-MMP-2 activity than IPA and healthy dogs. Meanwhile, dogs with IPA exhibited significantly higher activity of pro- and active MMP-9 than other groups. Activity levels in pro- and active MMP-9 in cRA and CCLR dogs were not significantly different from those in healthy controls. Different patterns of MMP-2 and MMP-9 activity may reflect the differences in the underlying pathological processes.